Clinical case of thrombotic microangiopathy in obstetric practice - M. N. Mochalova; T. E. Belokrinitskaya; T. V. Haven; E. M. Shifman; K. G. Shapovalov; S. V. Kostromitin (Сеченовский вестник, 2017)
Trombotic microangiopathy is heterogeneous group of the diseases united by a community of a histological and clinical implications at difference of pathogenetic mechanisms, presents clinical-morphological syndrome characterizing a lesion of vessels of a microcirculatory channel. Currently thrombotic microangiopathy include thrombotic thrombocytopenic purpura (TTP), atypical hemolytic uremic syndrome (aHUS), heparin-induced thrombocytopenia, HELLP-syndrome. One of the most important triggers of emergence of a thrombotic microangiopathy is pregnancy. The article describes the clinical observation of atypical hemolytic uremic syndrome in obstetric practice.